Experimental Study and Numerical Simulation of the Effect of Rigid Pile Composite Foundations on Slab Culverts - Xiqing Wang; Zhongju Feng; Siqi Wang; Wei Wang (Advances in Civil Engineering)
For culverts installed in soft soil, the rigid composite pile foundation is used for soil treatment, and the stresses around the culverts are complicated. Centrifuge experiments and numerical simulations are conducted to investigate the vertical earth pressures and soil settlement over a slab culvert under high backfill in soft soil, and the foundations are treated with rigid composite piles. The influences of lateral pile length and pile spacing on the earth pressures at the top of the culvert are analysed, and they have significant effects on the vertical earth pressure coefficients. It also indicates a strong correlation between the backfill height and the vertical earth pressure coefficients. For a high-backfill culvert, there is a uniform settlement surface where the settlement of the interior and exterior soil prisms is at the same level. According to the experiments, the height of the uniform settlement surface and the vertical earth pressures decrease with increasing the lateral pile length and pile spacing. Numerical simulations were conducted using finite element software Midas GTS to evaluate the performance of the experiments. Further, recommendations for selecting an appropriate pile composite foundation for slab culvert in soft soil are provided.